GEDOEL : A Powerful Regional Trade Facilitation Tool - Barragan, Fernando; Escalante, Ana (World Bank, Washington, DC, 2012)
Given the strong trade flows among the United States, Central America (Costa Rica, Honduras, Guatemala, Nicaragua, and El Salvador) and the Dominican Republic, the ratification of the Central America and Dominican Republic Free Trade Agreement (CAFTA-DR) represents an opportunity for the trade community in signatory countries to benefit from preferential tariff treatment through the correct application of rules of origin (ROO) and origin procedures a series of provisions at the heart of the CAFTA-DR that set forth the requirements for goods to be considered originating from a particular country and, therefore, to gain access to preferential tariff treatment. From an importer, exporter, or producer perspective, the key to benefiting from CAFTA-DR is the ability to access preferential tariff treatment, which relies on understanding and using the ROO, not in a theoretical sense but in a real, hands-on way that permits the correct categorization of goods. This smart lesson describes how the U.S. Agency for International Development (USAID)-funded Regional Trade Program for CAFTA-DR (CRT) developed an innovative information technology application to facilitate the understanding and use of complex rules of origin in order to make it possible for the trade community in CAFTA-DR countries to fully benefit from the agreement.